Are You Small? - Willems, Mo (New York Union Square Kids, 2024)
"Are YOU small? This tiny question allows readers to zoom in from an average-sized kid down to a single quark"--
Includes index.
Cover title.
Ages 3-5
Grades K-1
114126
Keywords: Size perception -- Juvenile literature; Picture books